2010
DOI: 10.1097/pts.0b013e3181fc98d7
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mode and Effects Analysis

Abstract: Objectives: To empirically compare 2 different commonly used failure mode and effects analysis (FMEA) scoring procedures with respect to their resultant failure mode scores and prioritization: a mathematical procedure, where scores are assigned independently by FMEA team members and averaged, and a consensus procedure, where scores are agreed on by the FMEA team via discussion.Methods: A multidisciplinary team undertook a Healthcare FMEA of chemotherapy administration. This included mapping the chemotherapy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Of those that were, severity ratings were different between the two groups. Similarly, discrepancies in HFMEA scores were found by Ashley and Armitage [19] who found differences in severity ratings determined by consensus between team members and those determined by averaging team members’ individual scores.…”
Section: Introductionsupporting
confidence: 56%
“…Of those that were, severity ratings were different between the two groups. Similarly, discrepancies in HFMEA scores were found by Ashley and Armitage [19] who found differences in severity ratings determined by consensus between team members and those determined by averaging team members’ individual scores.…”
Section: Introductionsupporting
confidence: 56%
“…For instance, FMEA was limited in the identification of external and environmental risks, as the failure modes were only identified according to the process steps shown in the system diagram provided, and no identification of external risks was allowed. As with the previous results, we recommended that the outputs from FMEA should not be used in isolation (Ashley and Armitage, 2010; Franklin et al, 2012; N. Shebl et al, 2012; Shebl et al, 2009), but should be treated valuable to support the overall risk identification practice.…”
Section: Capturing Requirements For the Proposed Risk Identification mentioning
confidence: 59%
“…FMEA was conducted in two teams to minimise the disruption to routine dispensing services at the study hospital and was successfully completed by both teams. Most FMEA studies found in the literature proceeded with one team [ 2 , 12 , 19 21 , 24 , 27 , 31 , 34 , 36 ]. Shebl et al, [ 15 ] reported a FMEA study conducted using two teams in two settings.…”
Section: Discussionmentioning
confidence: 99%